The tyranny of normal. (Economist, 2017)
The article offers information on the educational scenario of France. Topics discussed include the education policy enacted by French president Emmanuel Macron, the practice of uniform schooling by the country and the inequality prevalent in the country's education standardising system. Details regarding the computer programming school named 42 established in Paris, France are also provided.